PERPUSTAKAAN SEBAGAI AGEN PENDIDIKAN SEPANJANG HAYAT MELALUI PROGRAM KELAS BAHASA ASING DI LEMBAGA PEMASYARAKATAN PEREMPUAN IIA BANDUNG - Yustira, Nathania; Saleha Rodiah; Fitri Perdana (Nusantara Hasana Journal, 2026)
Lifelong education is a right for all from infancy to the end of life. It is closely associated with teaching and learning activities. The intellectual development program, particularly foreign language classes (English, German, and Mandarin) conducted in the library of the Class IIA Women’s Correctional Institution in Bandung, represents a form of non-formal education grounded in the principles of lifelong education. This study aims to examine the dynamics of lifelong education as manifested through foreign language learning programs facilitated by the library. The research employs a qualitative case study approach, with data collected through interviews, observations, and documentation. The findings indicate that the library supports lifelong education through educational activities by attempting to provide learning resources for inmates, despite their limited availability, fostering an intellectual atmosphere, offering adequate facilities and infrastructure, and supplying additional reading materials that encourage inmates to become lifelong learners. In this way, libraries in women's correctional institutions can become agents of lifelong education for inmates.